The puzzle master ebook A novel. - Trussoni, Danielle (2023)
Reality and the supernatural collide when an expert puzzle maker is thrust into an ancient mystery—one with explosive consequences for the fate of humanity—in this suspenseful thriller from the New York Times bestselling author of Angelology “This novel has it all and more. In the nimble, talented hands of Trussoni the pages fly.”—#1 New York Times bestselling author David Baldacci A BEST BOOK OF THE YEAR: The Washington Post, PopSugar, Bookreporter, CrimeReads All the world is a puzzle, and Mike Brink—a celebrated and ingenious puzzle constructor—understands its patterns like no one else. Once a promising Midwestern football star, Brink was transformed by a traumatic brain injury that caused a rare medical condition: acquired savant syndrome. The injury left him with a mental superpower—he can solve puzzles in ways ordinary people can’t. But it also left him deeply isolated, unable to fully connect with other people. Everything changes after Brink meets Jess Price, a woman serving thirty years in prison for murder who hasn’t spoken a word since her arrest five years before. When Price draws a perplexing puzzle, her psychiatrist believes it will explain her crime and calls Brink to solve it. What begins as a desire to crack an alluring cipher quickly morphs into an obsession with Price herself. She soon reveals that there is something more urgent, and more dangerous, behind her silence, thrusting Brink into a hunt for the truth. The quest takes Brink through a series of interlocking enigmas, but the heart of the mystery is the God Puzzle, a cryptic ancient prayer circle created by the thirteenth-century Jewish mystic Abraham Abulafia. As Brink navigates a maze of clues, and his emotional entanglement with Price becomes more intense, he realizes that there are powerful forces at work that he cannot escape.  Ranging from an upstate New York women’s prison to nineteenth-century Prague to the secret rooms of the Pierpont Morgan Library, The Puzzle Master is a tantalizing, addictive thriller in which humankind, technology, and the future of the universe itself are at stake.